Patient education for hyperphosphatemia management: Improving outcomes while decreasing costs? - Mirey Karavetian; Rana Rizk (The Korean Society of Nephrology, 2018)
The above article (https://doi.org/10.23876/j.krcp.2017.36.1.68) contains errors. The values of y axis in Fig. 3 should be corrected as following page. The authors would like to apologize for any inconvenience this has caused.